Jhumpa Lahiri’s Interpreter of Maladies as Postmodern Rupture on Classical Diaspora - Rai, Duryodhan (Journal of Development Review, 2023)
This research paper illumines how Jhumpa Lahiri’s short stories’ collection Interreter of Maladies presents postmodern diaspora as the discontinuity of classical diaspora. Classical/traditional diaspora sees homeland as irreplaceable place. The immigrants eventually return their homelands. Lahiri's version of diaspora differs from traditional mode of diaspora. As a well-known Indian American writer, Jhumpa Lahiri is pretty admired for her chronicle of Bengali immigrant experience. Though she portrays an attachment of immigrants with their homeland, they do not necessarily dream of returning home one day. They continuously strive to adjust themselves in new milieu. Lahiri’s characters in Interpreter of Maladies go on endeavoring to transform their sense of dislocation as their proper location. They constantly build up new identity using their memory combining with new ongoing experiences in new setting.